(untitled) (Nexus International Journal of Science and Education, 2024)
This qualitative-phenomenological study delved into the teaching experiences of educators at Don Juan dela Cruz Central Elementary School within the context of post-pandemic education. Employing Creswell's thematic analysis, the research used in-depth interviews and focus group discussions as data collection methods, involving 10 elementary teachers with a minimum of three years of teaching experience. These educators navigated the transition from online classes during the COVID-19 pandemic to various post-pandemic education models, including in-person teaching, hybrid, and distance learning. The study revealed that one of the elementary school teachers’ struggles was the students' learning loss because of the pandemic disruptions and explores internet and technological disparities that hinder students' participation in online learning. Additionally, the research delved into students' social and emotional unpreparedness, augmenting the struggles of teachers’ readjustment. While teachers faced these challenges, their coping strategies were emotional-focused coping strategies, schools and government’s interference, and high-speed internet connectivity which benefited the teaching and learning experiences. Lastly, this research provided valuable insights into the experiences of elementary school teachers in a post-pandemic education setting which include the flexibility of post-pandemic education. It is also seen as a time for teachers’ technological integration and digital literacy, and opportunity for stakeholders’ collaboration between one another. The findings can inform school principals and education policymakers in developing strategies to support teachers, address students’ learning loss, and bridge technological disparities. It also underscores the need for ongoing collaboration and support among stakeholders to create a flexible and inclusive post-pandemic education system.